Development of a mobile power plant for thawing frozen soils. (November 2019) - Sinitsyn, Anton; Mihin, Anton; Zaripova, Daniya
Abstract: The article proposes a new device for radiation-convective heating of working fluids, which can be used in particular for emergency and repair and construction works for heating of frozen soil, concrete, road surface and other building materials. The studies were carried out as part of implementation of the Innovation Assistance Fund for Energy Sector Enterprises.